(untitled) (International Journal of Food and Nutritional Sciences, 2023)
As a cutting-edge and very successful technique for environmental remediation, photocatalysis offers long-term solutions for reducing pollutants and enhancing environmental quality. By using light energy to activate semiconductor-based catalysts, this sophisticated oxidation process makes it possible to reduce heavy metal ions, break down organic contaminants, and transform hazardous gases into chemicals that are safe for the environment. Photocatalysis provides a cleaner, more energy-efficient option that is consistent with green chemistry principles, in contrast to traditional remediation methods that often demand significant energy input and produce secondary pollutants.